Design and Implementation of Laser Rangefinderfor Obstacle Height Monitoring on Line of Sight of Microwave Communication Link - Hudiono Hudiono; Mochammad Taufik; Ridho Hendra Yoga P.; Martono Dwi Atmadja (Program Pascasarjana Universitas Brawijaya, 2018)
A laser rangefinder is a device that uses laser light to determine the distance of an object. The working principle of this laser rangefinder is that the laser beam that is emitted to the object will be reflected back to the rangefinder, and the required propagation time of laser beam will be calculated to get the distance value. In this study, a laser rangefinder system was designed to be used as monitoring of obstacle height between the line of sight of a microwave communication link using a quadcopter, which is used as a top-viewer picture taker. The quadcopter was used as a device to carry the laser rangefinder to measure the obstacle height between the location points of near-end and far-end. The obstacle height reading results were transmitted using a 5.8 GHz wireless transceiver to the monitoring location in real time. The data received were then processed to be displayed in the form of obstacle height graph as a function of the line of sight communication distance. The test results show that the implementation of laser rangefinder technology has an accuracy of more than 90%.Keywords: Line of Sight, Laser Rangefinder, Near-end and far-end, Quadcopter, Obstacle